(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the revival of Cossacks in Katerinoslav region in August ñ November, 1917. Preconditions, reasons, a social base, and character of the Cossack movement are investigated. The author discloses the process of origin, rise and development of the Free Cossacks organizations including their legal registration. The numerous facts of active participation of the local population in the movement are presented.